Development of hepatic steatosis in male and female mule ducks after respective force-feeding programs - Atallah, Elham; Trehiou, Sabrina; Alquier-Bacquie, Valérie; Lasserre, Frédéric; Arroyo, Julien; Molette, Caroline; Remignon, Hervé (Frontiers in Physiology, 2024)
Male and female mule ducks were subjected to a force-feeding diet to induce liver steatosis, as it is generally done only with male ducks for the production of foie gras. The different biochemical measurements indicated that the course of hepatic steatosis development was present in both sexes and associated with a huge increase in liver weight mainly due to the synthesis and accumulation of lipids in hepatocytes. In livers of males and females ducks, this lipid accumulation was associated with oxidative stress and hypoxia. However, certain specific modifications (kinetics of lipid droplet development, hepatic inflammation) indicate that females may tolerate force-feeding less well, at least at the hepatic level. This is in contradiction with what is generally reported concerning hepatic steatosis induced by dietary disturbances in mammals but could be explained by the very specific conditions imposed by force-feeding. Despite this, force-feeding female ducks seems entirely feasible provided that the final quality of the product is as good as that of the males, which will remain to be demonstrated in future studies.